A single nucleotide polymorphism in the NCF1 gene leading to reduced oxidative burst is associated with systemic lupus erythematosus. Issue 9 (12th June 2017) - Olsson, Lina M; Johansson, Åsa C; Gullstrand, Birgitta; Jönsen, Andreas; Saevarsdottir, Saedis; Rönnblom, Lars; Leonard, Dag; Wetterö, Jonas; Sjöwall, Christopher; Svenungsson, Elisabet; Gunnarsson, Iva; Bengtsson, Anders A; et al.
Abstract : Objectives: Ncf1 polymorphisms leading to low production of reactive oxygen species (ROS) are strongly associated with autoimmune diseases in animal models. The human NCF1 gene is very complex with both functional and non-functional gene copies and genotyping requires assays specific for functional NCF1 genes. We aimed at investigating association and function of the missense single nucleotide polymorphism (SNP), rs201802880 (here denoted NCF1-339) in NCF1 with systemic lupus erythematosus (SLE). Methods: We genotyped the NCF1-339 SNP in 973 Swedish patients with SLE and 1301 controls, using nested PCR and pyrosequencing. ROS production and gene expression of type 1 interferon-regulated genes were measured in isolated cells from subjects with different NCF1-339 genotypes. Results: We found an increased frequency of the NCF1-339 T allele in patients with SLE, 11% compared with 4% in controls, OR 3.0, 95% CI 2.4 to 3.9, p=7.0×10 −20 . The NCF1-339 T allele reduced extracellular ROS production in neutrophils (p=0.004) and led to an increase expression of type 1 interferon-regulated genes. In addition, the NCF1-339 T allele was associated with a younger age at diagnosis of SLE; mean age 30.3 compared with 35.9, p=2.0×1 −6 . Conclusions: These results clearly demonstrate that a genetically controlled reduced production of ROS increases the risk of developing SLE and confirm the hypothesis that ROS regulate chronic autoimmune inflammatory diseases.